Kesejahteraan Perempuan di Indonesia Dalam Perspektif Hukum dan Hak Asasi Manusia - Reinier S.D. Sitanala (Faculty of Law, Universitas Pattimura, 2012)
Nature and feel easting woman altered difficult Indonesia of drastic. Modernization desired by Indonesian nation is not westernization, while culture nation represent its kindness of Indonesia people. In Outline Bow State affirmed that culture form as Personal personification Human being Indonesia have to value live and ethics meaning which is Pancasila head. Emancipation Woman of Indonesia pushing to get the opportunity which is equal to man clan all area still coloured by sosiology factor, culture and custom representing value live and ethics meaning. Therefore, condition of woman in Indonesia in so many life aspect it is true still have to be fought for farther. existence constitutional Rights along with its UU supporter will not meaning many if perception about woman not be strived to be altered. Struggle to increase prosperity of woman not solely become mere woman clan concern, however also entireall citizen